Elastic, Conductive Coating Layer for Self‐Standing Sulfur Cathode Achieving Long Lifespan Li–S Batteries. Issue 25 (19th May 2020) - Wang, Wenqiang; Wang, Dongya; Wang, Guiyou; Zheng, Mengyao; Wang, Gengchao
Abstract: The shuttle of polysulfide and severe volume change of sulfur cathodes, are the bottlenecks in the practical application of lithium–sulfur batteries, and need to be solved through further exploration of simple and scalable strategies. Herein, an elastic and conductive coating layer is designed and synthesized, by combining water soluble conducting polymer modified carbon nanotubes (PASANTs) with crosslinked waterborne polyurethane ( c WPU). It shows high electronic conductivity and excellent resilience. As a result, a lithium–sulfur battery with c WPU/PASANTs coated cathode is able to achieve an outstanding cycle stability with a capacity of 70.8% after 500 cycles at 0.5C and an excellent rate performance (specific capacity of 1130 mAh g −1 at 0.1C and maintain 68.2% at 2C). This work embodies a systematic design concept, which shows the application prospects of large‐scale production, and is expected to be further applied to other easily pulverized high‐specific‐capacity materials such as silicon and tin. Abstract : This work reports an elastic and conductive coating layer, by combining a water soluble conducting polymer modified carbon nanotubes with waterborne polyurethane for the first time. Thanks to the elastic confinement and accelerated lithium polysulfide conversion enabled by the coating layer, a lithium–sulfur battery with greatly improved cycle stability is realized.